Liver Injury with Features Mimicking Autoimmune Hepatitis following the Use of Black Cohosh. (6th December 2009) - Guzman, Grace; Kallwitz, Eric R.; Wojewoda, Christina; Chennuri, Rohini; Berkes, Jamie; Layden, Thomas J.; Cotler, Scott J.
Abstract : There are a growing number of cases detailing acute hepatic necrosis in patients taking black cohosh ( Cimicifuga racemosa ), an over-the-counter herbal supplement for management of menopausal symptoms. Our aim is to illustrate two cases of liver injury following the use of black cohosh characterized by histopathological features mimicking autoimmune hepatitis. Both patients reported black cohosh use for at least six months and had no evidence of another cause of liver disease. Their liver biopsies showed a component of centrilobular necrosis consistent with severe drug-induced liver injury. In addition, the biopsies showed characteristics of autoimmune-like liver injury with an interface hepatitis dominated by plasma cells. Although serum markers for autoimmune hepatitis were not particularly elevated, both patients responded to corticosteroids, supporting an immune-mediated component to the liver injury. Liver injury following the use of black cohosh should be included in the list of differential diagnoses for chronic hepatitis with features mimicking autoimmune hepatitis.